Tank costs for domestic rainwater harvesting in East Africa - Parker, Alison; Cruddas, Peter; Rowe, Nick; Carter, Richard; Webster, James (Thomas Telford, 2012)
Rainwater harvesting from hard roofing can provide safe water to meet the basic domestic needs of several hundred million people in low-income countries. However, rainwater harvesting has a higher household cost than other low-technology water supplies such as protected springs. The storage tank is the most expensive part of the infrastructure required for rainwater harvesting: reducing this cost will enable rainwater harvesting to become a viable water source for many more households in low-income countries. This paper assesses the overall costs and different cost components of rainwater storage tanks. Costs are compared across a selection of tanks prefabricated in factories in Uganda, Kenya and the UK and constructed in situ in Uganda. Constructed tanks were always found to be cheaper than prefabricated ones. Tank size was an important factor, and it was found that tank cost per litre decreases as size increases. For all tank types, materials were the greatest cost.